The Path Towards Novel Varieties: Investigating Phenotypic-Genetic Diversity in New Promising Egyptian Rice Lines - Waleed A. Almasoud; Mahmoud Abdel-Sattar; Saber Sedeek; Amgad A. Elgammaal; Nouran El-Refaee; Ibrahem A. Ramadan; Dina Abdulmajid; Hail Z. Rihan (Agronomy)
Rice (Oryza sativa L.) has an impressive range of phenotypic and genetic diversity, making it an important crop for global food security. Since rice phenotypic and genetic diversity are essential for enhancing the sustainability of rice production, an understanding of these variations is crucial for breeding efforts. Numerous factors, such as plant height, panicle number, grain properties, etc., exhibit phenotypic diversity in rice. Moreover, genetic diversity is essential for breeding and enhancing rice in multiple manners. This research investigates the phenotypic diversity of thirteen promising lines relative to their parents. Since the genetic effect reflects the plant’s phenotype, forty SSR markers were used to investigate the genotypic diversity. Generally, six promising genotypes produced much better grain yields than their parents. Across two years, the number of filled grains panicle−1 and the number of unfilled grains panicle−1 had the highest phenotypic and genotypic coefficients of variability percentage. The challenges towards novel variety with distinct characteristics were met in several promising lines under examination, which showed a significant and positive association between the grain yield and the number of panicles per plant, the number of filled grains per panicle, and the 1000-grain weight. Furthermore, five SSR markers were discovered to be polymorphic during the genetic diversity investigation, and the genotypes were classified into five clusters based on SSR marker data. The findings, together with further details, can be used to release novel and unique varieties.